A fast robust geometric fitting method for parabolic curves. - López-Rubio, Ezequiel; Thurnhofer-Hemsi, Karl; Blázquez-Parra, Elidia Beatriz; De-Cózar-Macías, Óscar; Ladrón-de-Guevara-Muñoz, María del Carmen (Elsevier, 2018)
Fitting discrete data obtained by image acquisition devices to a curve is a common task in many fields of science and engineering. In particular, the parabola is some of the most employed shape features in electrical engineering and telecommunication applications. Standard curve fitting techniques to solve this problem involve the minimization of squared errors. However, most of these procedures are sensitive to noise. Here, we propose an algorithm based on the minimization of absolute errors accompanied by a normalization of the directrix vector that leads to an improved stability of the method. This way, our proposal is substantially resilient to noisy samples in the input dataset. Experimental results demonstrate the good performance of the algorithm in terms of speed and accuracy when compared to previous approaches, both for synthetic and real data.
Keywords: Ajuste de curvas; Geometría analítica; Parabolic fitting; Geometric curve fitting; Noise; Minimization of absolute errors; Robust estimation